Effect of acid deamidation-alcalase hydrolysis induced modification on functional and bitter-masking properties of wheat gluten hydrolysates. (30th March 2019) - He, Wenmeng; Yang, Ruijin; Zhao, Wei
Highlights: Alcalase was the most efficient protease to hydrolyze wheat gluten. Properties of wheat gluten hydrolysates prepared by alcalase were improved. Properties of wheat gluten hydrolysates prepared by acid deamidation-alcalase hydrolysis were enhanced. Citric acid deamidation-alcalase hydrolysis wheat gluten hydrolysates showed the best bitter-masking property. Abstract: The low solubility of wheat gluten (WG) considerably limits its application. Owing to its high hydrolytic efficiency, alcalase was the protease selected for the enzymatic hydrolysis of WG. The functional properties of WG hydrolysate prepared by alcalase (AHWG) with a hydrolysis degree (DH) of 10% were better than those with DH 5% and DH 15%. The application of AHWG was hindered by its bitterness. To mask the bitterness of AHWG, WG was respectively deamidated with acetic acid, tartaric acid, and citric acid, followed by being hydrolyzed by alcalase to DH 10%. The citric acid deamidation-alcalase hydrolysis WG hydrolysate (CDAH) exhibited the best functional properties. Partial least squares regression analysis results indicated that CDAH exhibited an enhanced bitter-masking property attributable to a high content of umami taste amino acids (glutamic acid and aspartic acid). Thus, CDAH showed the greatest potential as a modified WG product to expand the application of WG.